2023
DOI: 10.1128/aem.02173-22
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide in Hydroxylamine Oxidation by Ammonia-Oxidizing Bacteria

Abstract: Ammonia oxidation by chemolithoautotrophic ammonia-oxidizing bacteria (AOB) is thought to contribute significantly to global nitrous oxide (N 2 O) emissions and leaching of oxidized nitrogen, particularly through their activity in nitrogen (N)-fertilized agricultural production systems. Although substantial efforts have been made to characterize the N metabolism in AOB, recent findings suggest that nitric oxide (NO) may play an important mechanistic role as a free intermediate of hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…It has been reported that low concentrations of PTIO have a strong inhibitory effect on AOA rather than AOB ( Sun et al, 2022 ). For example, under the condition of 100 μM PTIO, PTIO can inhibit the ammonia oxidation process by inhibiting AOA ( Duan et al, 2018 ; Choi et al, 2023 ), and thus it was used to selectively inhibit the activity of AOA in the presence of AOB ( Kits et al, 2019 ). 3,4-dimethylpyrazole phosphate (DMPP) is a highly soluble compound with high stability and persistent suppression effects ( Li et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that low concentrations of PTIO have a strong inhibitory effect on AOA rather than AOB ( Sun et al, 2022 ). For example, under the condition of 100 μM PTIO, PTIO can inhibit the ammonia oxidation process by inhibiting AOA ( Duan et al, 2018 ; Choi et al, 2023 ), and thus it was used to selectively inhibit the activity of AOA in the presence of AOB ( Kits et al, 2019 ). 3,4-dimethylpyrazole phosphate (DMPP) is a highly soluble compound with high stability and persistent suppression effects ( Li et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…While nitrate addition might stimulate both types of methanotrophs in paddy soil, ammonium addition only enriched type I methanotrophs while suppressing the growth of type II methanotrophs (Hu and Lu, 2015). While the methanotrophic strains lacking hydroxylamine oxidoreductase (HAO) are poor nitrifiers, the HAO-expressing strains may effectively oxidize ammonia (Nyerges and Stein, 2009;Stein and Klotz, 2011;Choi et al, 2023). Methane monooxygenases or ammonia monooxygenases linked to membranes oxidize ammonium in strains carrying the HAO gene, producing the intermediate hydroxylamine (Mohammadi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%